Population-based Incidence of Myopericarditis After COVID-19 Vaccination in Danish Adolescents. Issue 1 (January 2022) - Nygaard, Ulrikka; Holm, Mette; Bohnstedt, Cathrine; Chai, Qing; Schmidt, Lisbeth Samsø; Hartling, Ulla Birgitte; Petersen, Jens Jakob Herrche; Thaarup, Jesper; Bjerre, Jesper; Vejlstrup, Niels Grove; Juul, Klaus; Stensballe, Lone Graff
Abstract : In this prospective nationwide multicenter study from Denmark, myopericarditis after Pfizer-BioNTech mRNA COVID-19 vaccination was identified in 13 males and 2 females between May 15 and September 15, 2021, among 133, 477 vaccinated males and 127, 857 vaccinated females 12–17 years of age, equaling 97 males and 16 females per million. In conclusion, the incidence of myopericarditis after COVID-19 vaccination among males appears higher than reports from the United States.